A CASE AGAINST THE IDEA OF AN ALL–PURPOSE CONCEPT OF BUSINESS INCOME. - Johnson, Charles E. (The Accounting Review, 1954)
This article has attempted to establish the position that the significance of business income for corporate reporting lies primarily in its usefulness as a measure of corporate performance in diverting a stream of resources from the economy, and that it should be developed primarily to serve this function. It has been shown that concepts of income which will best serve as a tax base, as a factor in rate regulation, as an element of national income estimates, and as a basis for managerial decisions are all dependent upon specialized and divergent factors which are related to a variety of objectives. Each of these uses constitutes a special purpose problem by itself. As was suggested at the beginning of the discussion, an acceptance of this thesis is merely a prelude to the major work of deciding upon the business income concept and the means of measuring income so conceived which will best serve this basic need. The prelude in this case, however, should not be written after the major score is completed. Until an area of agreement is reached as to the purpose to be served by the measurement of business income the discussion of the business income problem proceeds in a vacuum.